El crimen organizado, su evolución e impacto en la seguridad ciudadana en la ciudad de Guayaquil Ecuador año 2021-2022. - Caicedo Gaibor, Damaris Anais (2023)
The present investigation is projected to point out about organized crime, its evolution and impact on citizen security in the city of Guayaquil Ecuador year 2021-2022. Referring to this issue is of great shock in today's society because it is a great problem that currently affects not only one country but several, since strategies and techniques are created every day that help organized crime cross borders and break limits. Certain factors influence for this to progress and it is unemployment, the lack of job opportunities, poverty and other factors, which have unbalanced society, and have allowed the identification of various actions that show that legal security in Ecuador, specifically in Guayaquil, worsens. since it not only causes fear, fear and insecurity in each of the inhabitants who have their home or family in said city. For this reason, in order to develop this research project, it was necessary to collect information through bibliographic sources, based on legal regulations, in addition to documents, books, videos, documentaries, in the opinion of several authors and television and radio media. Also, there was the help of thirty police officers who belong to the DINASED of the city of Guayaquil, an institution in charge of focusing on crimes that affect the legal good such as life through violent deaths. On the other hand, to obtain favorable and useful results for this research to be carried out in the best way, the survey was used as an important instrument. Which made it possible to show various significant aspects of the subject discussed above and thus achieve the objectives set and come to the conclusion that organized crime is part of a large network worldwide, which today harms the legal security of criminals Guayaquileños. Keywords: insecurity, hired assassins, legal certainty, violent deaths, shock.